O simb??lico nas propagandas de viagem: uma abordagem semi??tica - Cavalcante, Aline Carla Ribeiro (2016)
This research seeks to understand how tourism advertising understands the meaning of production process in their speeches, through the use of semiotic value elements, in order to sell travel destinations abroad. To this end, 232 ads were analyzed for companies that work in tourism, published in the magazine Viagem e Turismo, the segment leader in Brazil, to identify the semiotic elements most commonly used, and the imaginary of travel that, as a result, is being built and strengthened. The analysis examined the relation that the signs have with themselves, their objects and their interpretations. The theoretical foundation was made by the General Signs Theory and the categories of mind and nature defined by the American semiotic theory of Charles Sanders Pierce, and the semiotics of Russian culture. In the tourism field, the concepts presented by Susana Gastal and Jacques Wainberg, who found a relation between tourism, communication and imagination were used. Tourism advertising works in the imaginary of travel making use of semiotic elements that add value. In order to achieve the main objective of advertising, communication commitment is with the imaginary, not reality. The analysis of travel ads revealed their main strategy of persuasion: the seduction by the image, using firstness elements, because of their qualitative aspects, and thirdness, using the symbolic signs. By the use of the symbolic elements, images increased the qualities of tourist destinations, and complementary to that, the texts increased differentials and guarantees of services. This characteristic, so well displayed in the ads, may be a reflection of the tourism market which is currently engaged in extensive travel opportunities outside the circuit of agencies. Advertisements, and their ads as a way to answer, bet on messages that go beyond what the tourist destination has to offer, therefore, beyond the beauty of the destinations, other advantages that will also help in persuasion, as the operational characteristics. The trip is presented as a symbolic construction and this construction logic almost always reflects stereotypes in order to purpose clich?? emotions.